Light-Induced Al Plating on Si for Fabrication of an Ag-Free All-Al Solar Cell. (8th February 2021) - Ricci, Lewis; Tseng, Mao-Feng; Tao, Meng; Liu, Yunyu; Jiang, Fangdan; Xing, Guoqiang
Abstract : Light-induced electroplating of Al as the front electrode on the n-type emitter of Si solar cells is proposed as a substitute for screen-printed Ag. The advantages and disadvantages of Al over Cu as the front electrode are discussed. The power of a green laser used for patterning of the SiNx antireflection coating is optimized. Conditions for removal of laser damage and contamination on the laser-patterned surface are identified. The effect of plating temperature and post-annealing temperature on Al morphology and resistivity are investigated. Several plating additives are explored to improve the morphology and resistivity of the Al film. Nicotinic acid produces the lowest resistivity of 3.1 μ Ω-cm. However, the lowest contact resistivity between light-induced Al and Si is 69 mΩ-cm 2 due to laser-induced damage to the emitter. The Al film spikes through the thin n-type emitter when annealed at 500 °C causing cell failure. The process reproducibility is also poor due to atmospheric moisture.